Multi-Subject Collaborative Mechanism for Grassroots Public Safety Governance: A Case Study of the “2·18” Fireworks Explosion Accident in Xiangyang - Lu, Xi (International Journal of Social Sciences and Public Administration, 2026)
Grassroots public safety governance is a fundamental part of the modernization of national governance. The “2·18” fireworks and firecracker explosion accident in Xiangyang, Hubei Province in 2026 caused heavy casualties, exposing a systemic failure of community safety defenses. Drawing on collaborative governance theory, this paper constructs a three‑dimensional analytical framework of “actor - authority - interaction” to dissect the mechanisms of multi‑actor collaborative failure in the accident. The study finds that business entities have shifted from safety guardians to risk sources, with profit‑seeking behavior and a fluke mentality leading to institutional dysfunction. The administrative system is characterized by fragmented powers and responsibilities, where formalistic supervision fails to address substantive risks. The interaction among multiple actors is disconnected, and information silos together with misaligned incentives result in a “core‑periphery” differential structure of the collaborative network. Accordingly, this paper proposes a three‑in‑one optimization path: clarifying the list of powers and responsibilities, enabling collaboration through technology, and building a governance model based on common participation, shared responsibility, and collective benefits, so as to promote the transformation of grassroots safety governance from fragmentation to holistic collaboration.